Secret police files from the Eastern bloc : between surveillance and life writing - Glajar, Valentina; Lewis, Alison, 1958-; Petrescu, Corina L. (Studies in German literature, linguistics, and culture., 2016)
The communist secret police services of Central and Eastern Europe kept detailed records not only of their victims but also of the vast networks of informants and collaborators upon whom their totalitarian systems depended. These records, now open to the public in many former Eastern Bloc countries, reflect a textually mediated reality that has defined and shaped the lives of former victims and informers, creating a tension between official records and personal memories. Exploring this tension between a textually and technically mediated past and the subject/victim's reclaiming and retrospective interpretation of that past in biography is the goal of this volume. While victims' secret police files have often been examined as a type of unauthorized archival life writing, the contributors tothis volume are among the first to analyze the fragmentary and sometimes remedial nature of these biographies and to examine the subject/victims' rewriting and remediation of them in various creativeforms. Essays focus, variously, on the files of the East German Stasi, the Romanian Securitate (in relation to Transylvanian Germans in Romania), and the Hungarian State Security Agency. Contributors: Carol Anne Costabile-Heming, Ulrike Garde, Valentina Glajar, Yuliya Komska, Alison Lewis, Corina L. Petrescu, Annie Ring, Aniko Szucs. Valentina Glajar is Professor of German at Texas State University, San Marcos. Alison Lewis is Professor of German in the School of Languages and Linguistics, The University of Melbourne, Australia. Corina L. Petrescu is Associate Professorof German at the University of Mississippi.